Influence of manganite powder grain size and Ag-particle coating on the magnetocaloric effect and the active magnetic regenerator performance. (15th September 2015) - Turcaud, J.A.; Bez, H.N.; Ruiz-Trejo, E.; Bahl, C.R.H.; Nielsen, K.K.; Smith, A.; Cohen, L.F.
Graphical abstract: The magnetocaloric performance of La0.67 Ca0.27 Sr0.06 Mn1.05 O3 is investigated as a function of the powder grain size and also as a function of decoration of grains with highly conductive silver particulates as a coating layer. We demonstrate that the thermal and electrical conductivities can be significantly modified by the Ag-particle coating when the material is examined in sintered pellet form and we compare results with a second manganite composition La0.67 Ca0.33 MnO3 with significantly smaller grain size. However, we find that this microstructural engineering does not improve the performance of the active magnetic regenerator cycle using the silver decorated material in powder form. The regenerator performance is improved by the reduction of the powder grain size of the refrigerant which we attribute to improved thermal management due to increased surface to volume ratio. Abstract: The magnetocaloric performance of La0.67 Ca0.27 Sr0.06 Mn1.05 O3 is investigated as a function of the powder grain size and also as a function of decoration of grains with highly conductive silver particulates as a coating layer. We demonstrate that the thermal and electrical conductivities can be significantly modified by the Ag-particle coating when the material is examined in sintered pellet form and we compare results with a second manganite composition La0.67 Ca0.33 MnO3 with significantly smaller grain size. However, we find that this microstructural engineering does not improve the performance of the active magnetic regenerator cycle using the silver decorated material in powder form. The regenerator performance is improved by the reduction of the powder grain size of the refrigerant which we attribute to improved thermal management due to increased surface to volume ratio.